Automated eye blink detection and correction method for clinical MR eye imaging. Issue 1 (1st August 2016) - Wezel, Joep; Garpebring, Anders; Webb, Andrew G.; van Osch, Matthias J.P.; Beenakker, Jan‐Willem M.
Abstract : Purpose: To implement an on‐line monitoring system to detect eye blinks during ocular MRI using field probes, and to reacquire corrupted k‐space lines by means of an automatic feedback system integrated with the MR scanner. Methods: Six healthy subjects were scanned on a 7 Tesla MRI whole‐body system using a custom‐built receive coil. Subjects were asked to blink multiple times during the MR‐scan. The local magnetic field changes were detected with an external fluorine‐based field probe which was positioned close to the eye. The eye blink produces a field shift greater than a threshold level, this was communicated in real‐time to the MR system which immediately reacquired the motion‐corrupted k‐space lines. Results: The uncorrected images, using the original motion‐corrupted data, showed severe artifacts, whereas the corrected images, using the reacquired data, provided an image quality similar to images acquired without blinks. Conclusion: Field probes can successfully detect eye blinks during MRI scans. By automatically reacquiring the eye blink‐corrupted data, high quality MR‐images of the eye can be acquired. Magn Reson Med 78:165–171, 2017. © 2016 International Society for Magnetic Resonance in Medicine